(untitled) (CIPEEX, 2022)
IT IS NOTED THAT THE DEVELOPMENT OF THE TECHNOLOGY MARKET IN RECENT YEARS HAS BEEN INCREASING, BEING DRIVEN BY THE COVID-19 PANDEMIC. THE REALITY IS THAT MORE AND MORE STARTUPS HAVE BEEN CREATED TO SOLVE VARIOUS PROBLEMS AND THESE STARTUPS NEED QUALIFIED PROFESSIONALS TO MEET THEIR DEMANDS. IN CONTRAST TO THIS, DUE TO THE HEATING OF THIS MARKET, SEVERAL PEOPLE HAVE BEEN ATTRACTED TO IT, STARTING THEIR CAREERS ALREADY IN THIS MARKET OR EVEN MIGRATING FROM OTHER AREAS. THEREFORE, THERE IS A PROBLEM FOR THESE PROFESSIONALS TO FIND JOBS IN THE AREAS OF TECHNOLOGY AND TECHFINDER COMES TO SOLVE THIS PROBLEM. FOCUSED ON DEVELOPING ENTREPRENEURSHIP AND FACILITATING THE RECRUITMENT OF QUALIFIED PROFESSIONALS, THE TECHFINDER PLATFORM SEEKS TO BRING THESE SOLUTIONS TO SOCIETY. THE OBJECTIVE IS TO BRING A WELL-DEVELOPED CONCEPT ABROAD WITH A NEW FACE TO BRAZIL, CREATING AN ENVIRONMENT IN WHICH USERS CAN CREATE THEIR PORTFOLIO OF SERVICES THEY PERFORM, ASSEMBLE THEIR ONLINE CURRICULUM TO BE ABLE TO USE IT IN OTHER PLACES AND CREATE QUESTIONNAIRES. QUESTION-AND-ANSWER TOOL THAT CAN BE USED BY COMPANIES TO RECRUIT NEW EMPLOYEES. THE SCENARIO FOR THIS TYPE OF TOOL IN BRAZIL HAS LEFT SOMETHING TO BE DESIRED IN TERMS OF THE TECHNICAL PART IN WHICH SEVERAL SOLUTIONS USE MORE OUTDATED TECHNOLOGIES THAT HAVE NOT DELIVERED VALUE. THEREFORE, BY CONNECTING COMPANIES LOOKING FOR NEW PROFESSIONALS TO PEOPLE LOOKING FOR NEW OPPORTUNITIES, TECHFINDER AIMS TO SOLVE THIS PROBLEM QUICKLY AND WITHOUT BUREAUCRACY, THUS SOLVING THE PROBLEM OF COMPANIES AND NEW PROFESSIONALS IN THE TECHNOLOGY AREA.